Broken fragments and debris from the original temple assembled on the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the adhisthana on the southeast side. Relief carvings of geometric, flora and fauna motifs feature all around the adhisthana. Seen here is a carving of a peacock.